$Q$-conditional symmetry of a nonlinear two-dimensional heat-conduction equation - Andreeva, N. V.; Serov, N. I.; Tulupova, L. O. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the $Q$-conditional symmetry of a nonlinear two-dimensional heat-conduction equation. By using ansatzes, we obtain reduced equations.